EVALUATION AND MANAGEMENT OF POSTPARTUM HYPERTENSION IN A TERTIARY CARE HOSPITAL - MISHRA, SETUMA; Kaur, Parneet; PAL KAUR, SATINDER (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to study the causative factors of postpartum hypertension (PPHTN), time taken for control of blood pressure (BP) in postpartum period and to study the anti-hypertensive drugs used in control of PPHTN. Methods: The study was conducted for 1½ years. During the study, 190 women in postpartum period with high BP were enrolled in the study. A detailed record of history and general physical examination and local examination was done as per pro forma after written informed consent. Results: Out of 190 subjects, 168 had a history of hypertension (HTN) in the antenatal period, and the rest 22 went on to develop HTN in the postpartum period. Gestational HTN and preeclampsia were the most frequent types of hypertensive disorders seen among subjects. In 42.1% of patients, PPHTN developed after 48 h and in 23.7% of cases developed within 48 h. BP normalized post-delivery in 22.6% of subjects. The majority (74.1%) of subjects took tablet labetalol post-delivery. 62.1% of patients took anti-hypertensive for more than 7 days and were discharged on treatment with advice to follow-up. 15.3% took treatment for <7 days. No treatment was required by 22.6% of subjects. Conclusion: Our data identified a high prevalence of PPHTN. We found a significant correlation between the levels of severity of antepartum BP with the level of severity of postpartum BP. Monitoring of HTN is important in the postpartum period for all patients as the majority develop hypertension after 48 h.